(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
During the healthcare system reforms in Uzbekistan, child health protection has become one of the central priorities. Strengthening measures to safeguard children’s health and scientifically studying the historical experience in this field allow for conclusions that are highly relevant to contemporary society. This article examines the main initiatives undertaken in the Kashkadarya region to improve children’s health, as well as the establishment and development of modern medical centers.